2019
DOI: 10.1111/jog.13912
|View full text |Cite
|
Sign up to set email alerts
|

Is echocardiography necessary for all single umbilical artery fetuses? A retrospective study in a selected Chinese population

Abstract: Aim Previous evidence on the relationship between single umbilical artery (SUA) and congenital heart disease (CHD) is controversial. We thus conducted a retrospective study to explore the potential risk factors associated with CHD in SUA fetuses, and verify if all these SUA fetuses should be referred for detail fetal echocardiography. Methods We reviewed medical records of SUA fetuses referred to Xinhua Hospital for fetal echocardiography between September 2009 and February 2014. All the pregnancies were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
0
14
1
Order By: Relevance
“…This may result from the fact that when a structural or chromosomal abnormality is detected, the patient is subject to more detailed fetal anatomic screening, which heightens the possibility of detecting SUA. Unlike previous studies which found genitourinary or gastrointestinal system anomalies as the second most common anomaly, [10,22] we found fetal central nervous system anomalies as the second most frequent group of anomalies. Similar to previous studies, in this study, cardiac anomalies were the most commonly detected abnormalities (24.3%, 20/82).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This may result from the fact that when a structural or chromosomal abnormality is detected, the patient is subject to more detailed fetal anatomic screening, which heightens the possibility of detecting SUA. Unlike previous studies which found genitourinary or gastrointestinal system anomalies as the second most common anomaly, [10,22] we found fetal central nervous system anomalies as the second most frequent group of anomalies. Similar to previous studies, in this study, cardiac anomalies were the most commonly detected abnormalities (24.3%, 20/82).…”
Section: Discussioncontrasting
confidence: 99%
“…The frequency of detected karyotypic abnormalities revealed in this study is comparable with other studies, which ranged from 1.3% to 15.3%. [10,[22][23][24][25] However, the number of our patients who consented to genetic tests was relatively low, which may not reflect the true percentages of genetic abnormalities. Similar to previous studies, there were no karyotypic abnormalities in patients with iSUA.…”
Section: Discussionmentioning
confidence: 90%
“…6 Strengths of our study include use of data from both our single center institution as well as data from 4 other publications over the last 9 years. 5,[10][11][12] This allowed both direct comparison of our current data with those across the country and yielded summary predictive characteristics. Our high positive predictive value is likely associated with our high prevalence of cardiac abnormalities detected in our patient population (38% vs.1% reported in the general population).…”
Section: Discussionmentioning
confidence: 99%
“…4 However, recent studies have questioned the need for additional imaging in the context of isolated SUA. 5 Given the need to minimize anxiety and unnecessary interventions, it is important to understand if fetal echocardiograms are necessary in the fetus with isolated SUA.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although an SUA is thought to have a high association with fetal anomalies, including congenital heart disease (CHD), several studies in low-risk or mixed risk populations have shown that an isolated SUA (without extracardiac or genetic abnormalities) is not associated with an increased risk of CHD. [2][3][4][5] Furthermore, as major cardiac defects are detectable in standard obstetric screening with sensitivity as high as 90%, 6 the need for dedicated fetal echocardiography in an isolated SUA has been questioned.…”
mentioning
confidence: 99%